Effect of Different Concentrations of Sucrose and Honey on the Physiochemical and Sensory Properties of Strawberry Leather - Khan, Arsalan; Kaleem, Muhammad; Qazi, Ihsan Mabood; Khan, Muhammad Ali; Hussain, Ibrar; Ayub, Muhammad; Shinwari, Abid Shah; Shah, Falak Naz; *, Ata Ur Rehman (Biological Sciences - PJSIR, 2017)
The aim of the present research work was to study the effect of different levels of sucrose and honey content on strawberry leather stored at room temperature for a total period of 90 days. The sucrose and honey was added at the level of 300:0, 250:50, 200:100, 150:150, 100:200, 50:250 and 0:300, representing each treatment. The prepared strawberry leather were analysed physiochemically for pH, acidity, ascorbic acid, reducing and non-reducing sugar content, sugar acid ration and organoleptically for colour, taste, texture and overall acceptability for a total period of 90 days. Statistical results revealed that treatment and storage interval had a significant (P< 0.05) effect on both physiochemical and organoleptic evaluation. Results also revealed that the decrease occurred in moisture content from (18.17-13.53%), pH (3.58 to 3.43), ascorbic acid (34.41 to 25.53), non-reducing sugar (5.09 to 4.85), sugar-acid ratio (71.03-65.37%), and sensory evaluation included colour (8.17 to 5.10), texture (8.31 to 5.69), taste (8.37 to 6.04) and overall acceptability (8.37 to 5.61), while increase was found in total acidity (1.137-1.267%), total soluble solid (80.96 to 83.04 °Brix) and reducing sugar (19.09-19.45%) during storage. The maximum mean values were observed for moisture in SL5 (16.37), ascorbic acid SL4 (31.59), pH SL4 (3.57), titratable acidity SL4 (1.230), total soluble solid SL4 (82.80), total solid SL4 (82.80), reducing sugar SL4 (26.47), non-reducing sugar SL1 (6.20), colour SL4 (7.13), texture SL4 (7.54), taste SL4 (7.79), overall acceptability SL4 (7.5) and sugar-acid ratio SL6 (70.76). Among all the treatments, T4 was found to be the best both physiochemically and organoleptically.